Pendapatan dasar Melalui Bantuan Sosial PKH Sebagai Upaya Peningkatan Ekonomi Masyarakat Miskin; Studi Kasus Analisis Kapital Sosial Masyarakat Dusun Sade, Lombok, NTB - Muhammad Imam Saputra (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The existence of good relations through a close level of trust in the formation of social capital between the community and the government will increase the success of a program. The government's understanding of the real needs of the community, the community is also able to optimize program interventions which will result in work harmony between the government and the community. The fulfillment of basic needs which is the main polemic can be met with social security with the concept of a pendapatan dasar. The existence of this idea is expected to increase public confidence in the government. The income obtained through social assistance in the form of cash will provide unconditional life insurance which will later change the mindset and behavior of the community in applying other assistance programs. This meeting point will later answer the global challenge in mobilizing the community to continue to carry out production activities. This study uses a qualitative approach which is located in the tourism area of Dusun Sade, Lombok. In-depth interviews were conducted with representatives of indigenous peoples, traditional leaders and representatives from the government. The information to be obtained is the certainty of social assistance that is able to increase the trust of the people of Sade Hamlet and the government is optimizing the social assistance program as a form of government effort to reactivate the economy in Sade Hamlet Keywords: Basicn Income, Social Capital, Indigenous People, Sade Hamlet AbstrakAdanya hubungan baik melalui tingkat kepercayaan yang erat dalam pembentukan kapital sosial antara masyarakat dengan pemerintah akan meningkatkan keberhasilan suatu program. Pemahaman pemerintah akan kebutuhan riil masyarakat dan sebaliknya masyarakat mampu mengoptimalkan intervensi program mampu menghasilkan keselarasan kerja antara pemerintah dengan masyarakat. Pemenuhan kebutuhan dasar yang menjadi polemik utama dapat dipenuhi dengan jaminan sosial yang berkonsep pada pendapatan dasar yang universal. Adanya gagasan ini diharapkan mampu meningkatkan kepercayaan masyarakat akan pemerintah. Pendapatan yang didapatkan melalui bantuan sosial berbentuk cash akan memberikan jaminan hidup tanpa syarat yang nantinya akan mengubah pola pikir dan perilaku masyarakat dalam mengaplikasikan program bantuan lainnya. Titik temu inilah yang nantinya menjawab tantangan global dalam memobilisasi masyarakat untuk terus melakukan aktivitas produksi. Studi ini menggunakan pendekatan kualitatif yang berlokasi di kawasan pariwisata Dusun Sade, Lombok. Wawancara mendalam dilakukan kepada perwakilan masyarakat adat, tokoh adat dan perwakilan dari pemerintah. Informasi yang ingin didapat berupa kepastian bantuan sosial yang mampu meningkatkan trust/kepercayaan masyarakat Dusun Sade dan pemerintah mengoptimalkan program bantuan sosial sebagai bentuk upaya pemerintah menggerakkan kembali perekonomian di Dusun Sade. Kata Kunci: Kapital Sosial, Pendapatan dasar, Masyarakat Adat, Dusun Sade